Multidimensional poverty analysis: an application for the states of Brazilian´ s Southeastern region in the years of 2005, 2011 and 2015 - Ferreira, Taís Regina da Silva; Giuberti, Ana Carolina; Zambon Monte, Edson (Revista Economia Ensaios, 2024)
Based on the theoretical contribution of the Capabilities Approach and using the Alkire-Foster method as a methodological reference, this article presents a multidimensional poverty index for the states of the Southeast region in the years 2005, 2011, and 2015, using data from the National Sample Survey of Households (PNAD). However, unlike other studies, the contribution of this article is to identify the indicators of greatest need for individuals residing in this region. The results indicate that Rio de Janeiro and São Paulo were the states that presented the lowest poverty rate and an increase in the intensity of poverty in the years researched. Furthermore, considering the four states examined, the most significant deprivations are not linked to income but rather to the control over one’s environment.